Empirically Bounding of Space Booms with Tape Spring Hinges - A.L. Jennings; J. Black; C. Allen (Shock and Vibration)
Self-deploying structures seek to provide a compact launch package for large, lightweight satellite booms. One self-deploying method is a foldable tape spring. This paper examines the large scale behavior of a boom attached by a tape spring hinge during mock deployments. A boom attached by tape spring to a rigid stand was released and the boom bounced up to 60° before coming to rest (as opposed to snap-through behavior). These large amplitude bounces can cause the boom to collide with sensors, other booms or arrays causing damage or preventing full deployment. Results show the first bounce of deployment is nearly bounded by a four parameter ellipse. The ellipses of similar folds are similar also, suggesting that a model can be developed. Free-fall tests simulating the free-free condition found in microgravity also show similar elliptical motion. Envelopes that bound the extents of the boom motion allow for collisions to be prevented by adjustment of the design.